Pendampingan Pastoral Kepada Perempuan Korban KDRT dI HKBP - Mangara Pakpahan (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2020)
This research is intended to give attention to members of the congregation, especially women (wives) victims of Domestic Violence (Domestic Violence) in the HKBP church, especially HKBP Duren Sawit. Cases of domestic violence experienced by women as victims greatly affect their personal lives and relationships to others. Women victims of domestic violence suffer physical and psychological injury. This happens as a result of the violence and suffering experienced. Based on this the authors conducted research and provide assistance through pastoral assistance that is sustaining, reconciling and healing. Supporting is to strengthen women victims of domestic violence who are experiencing a crisis so that they do not dissolve in their sadness, disappointment and fear. Reconciling is helping women victims of domestic violence build and renew their relationships with God and others. Healing is overcoming the damage suffered by women domestic violence, returning to wholeness and leading it to a better direction. Sampling was carried out for five female congregation (wife) victims of domestic violence at the HKBP Duren Sawit church. Pastoral assistance from the Duren Sawit HKBP church to victims of domestic violence has never been done well and seriously. This makes the congregation of victims of domestic violence despair because of the violence and suffering they experienced, thus making it stay in a feeling of confusion and fear. As a result there are congregation victims of domestic violence who actually go outside the church, to seek protection in the hope of receiving strength and recovery. Crisis counseling is a form of service that the church can do to women victims of domestic violence, so that they can experience strengthening, reconciliation, and healing from the violence and suffering experienced.